1996
DOI: 10.1007/bf00134181
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of aspartic proteinases: Application of transition-state analogue theory

Abstract: Applying the semiempirical MO methods AM1 and PM3 as well as the density functional theory to the model of the catalytic site composed of ca. 160-190 atoms, we have carried out studies aimed at the explanation of three aspects of the mechanism of action of aspartic proteinases: the site of dissociation within the catalytic diad COOH/COO- (i) in the free enzyme and (ii) in the Michaelis complex, and (iii) the energy changes associated with the catalytic paths. We have found that the state of dissociation within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Because the binding interface of CatD and its ligand is similar to that of plasmepsin II-pepstatin, we protonated His77 and Glu260 . The electronic structure calculations on the penicillopepsin−substrate complex suggested that the Asp33 outer oxygen was protonated . Because of the high structural similarity at the active site among the aspartic proteinases, we chose the Asp33 outer oxygen to be protonated in CatD−inhibitor complexes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the binding interface of CatD and its ligand is similar to that of plasmepsin II-pepstatin, we protonated His77 and Glu260 . The electronic structure calculations on the penicillopepsin−substrate complex suggested that the Asp33 outer oxygen was protonated . Because of the high structural similarity at the active site among the aspartic proteinases, we chose the Asp33 outer oxygen to be protonated in CatD−inhibitor complexes.…”
Section: Methodsmentioning
confidence: 99%
“…38 The electronic structure calculations on the penicillopepsin-substrate complex suggested that the Asp33 outer oxygen was protonated. 39 Because of the high structural similarity at the active site among the aspartic proteinases, we chose the Asp33 outer oxygen to be protonated in CatD-inhibitor complexes. Seven ligands were chosen from the combinatorial libraries of CatD inhibitors with the K i values ranging from nanomolar to micromolar.…”
Section: Molecular Mechanics Model Of the Inhibitorsmentioning
confidence: 99%
“…Subsequently, similar characteristics were reported in a crystallographic analysis of a complex between the human immunodeficiency virus type 1 (HIV-1) proteinase and its competitive inhibitor, a C 2 -symmetric phosphinate . This working model of the aspartyl proteinases complexed with transition-state analogues has recently received more support from crystal structure analyses such as those of pepsin, rhizopuspepsin, and endothiapepsin and from Fourier transform infrared spectroscopic studies. , In addition, an energetic analysis for such a catalytic pathway suggested that electronic effects are mainly responsible for the relative reduction of energy of the intermediates and possibly transition states on the catalytic reaction path …”
Section: Introductionmentioning
confidence: 70%